2006
DOI: 10.1111/j.1600-0765.2005.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid levels of calprotectin and myeloperoxidase during therapy for generalized aggressive periodontitis

Abstract: The correlations between calprotectin and MPO indicate that PMNs are a major contributor to the calprotectin content in gingival crevicular fluid of severely affected sites. Calprotectin levels in gingival crevicular fluid and their changes reflect periodontal inflammation as well as the clinical treatment outcome. A prognostic potential of this marker substance remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 42 publications
5
65
3
6
Order By: Relevance
“…Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients. Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients. Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47].…”
Section: Discussionsupporting
confidence: 83%
“…Although MPO is involved in the pathogenesis of infl ammatory periodontal diseases and pancreati c cancer, it is also found in clinically healthy sites in lower levels than the periodentally diseases sites 9,13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…GCF sampling and processing were done as has been described in detail elsewhere 12 . MPO acti vity (GM) is analysed as previous studies 13 . Relati onships between GM; probing depths and bleeding on probing, were analysed using a performed during SPSS (version 11.0, Chicago, USA).…”
Section: Rai -Gingival Crevicular Fluid Myeloperoxidase In Periodontimentioning
confidence: 99%
See 1 more Smart Citation
“…A MPO tem sido apresentada como um marcador da DP no GCF (Kaner, Bernimoulin et al 2006;Marcaccini, Meschiari et al 2010), porém ainda é pequeno número de trabalhos que mostram a MPO na STE e sua relação com a DP (Sakamoto, Fujii et al 2008). …”
Section: Doença Periodontalunclassified